Dismissal of Regional Heads in The Context of National Strategic Programs: A Perspective on Unitary State and Democracy - Rizqiyanto, Naufal; Suqiyanto; Adawiyah, Robiatul (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
The dismissal of regional heads is a complex issue in Indonesian governance. Non-compliance with national strategic programs is considered a serious offence that impacts national stability and development. In the context of a unitary state, the implementation of national policies must be harmonised at all levels of government. However, from a democratic perspective, the dismissal of regional heads must go through a transparent and accountable mechanism. This study aims to analyse the mechanism for dismissing regional heads who do not implement national strategic programs from the perspective of a unitary state and democracy. The method used is a normative legal research method with a descriptive-analytical approach. Data is obtained through literature study and analysis of legal documents. The results show that the dismissal of regional heads can strengthen the unity of the state by ensuring that national policies are consistently implemented. However, the mechanism must pay attention to democratic principles, including fair legal process, transparency, and accountability. This study concludes that the dismissal of regional heads who do not implement national strategic programs can be justified to maintain the unity of the country, provided that it is in accordance with democratic principles. Recommendations include improving mechanisms for monitoring and evaluating the implementation of national strategic programs and increasing dialogue between the central and local governments.